Enhancing Simulation Training Through the Utilization of Transas Engine Room Simulator for Marine Engineering Students at CTU – Carmen - Apor, Monette D.; Flores, Jelissa G.; Chin, Dindo M. (Future Science / FSH-PH Publications, 2025)
This study explores the use of the TRANSAS Engine Room Simulator (ERS) to enhance simulation-based training for third-year Marine Engineering students at Cebu Technological University – Carmen Campus. It investigates how simulation technology bridges the gap between theoretical knowledge and practical skills in the maritime industry. The research specifically evaluates the ERS’s effectiveness in skill development, considers the influence of students’ socio-demographic profiles, and identifies areas for improvement in simulation training. A descriptive-comparative research design with a quantitative approach was used, involving surveys of third-year Marine Engineering students. Data collected included socio-demographic information, technological knowledge of key operations (e.g., generator synchronization, boiler firing sequence), and simulator handling skills. Findings show that the Engine Room Simulator (ERS) significantly improves student engagement, knowledge retention, and operational proficiency. However, gaps were identified in areas such as troubleshooting and data interpretation, suggesting the need for enhanced training modules. The results highlight the importance of integrating advanced simulation technologies into maritime education to support both theoretical learning and hands-on competence. The study recommends tailoring training modules to students' backgrounds, regularly updating simulator content, and incorporating targeted instruction in weaker skill areas. These improvements will help develop a more effective simulation training program, better preparing students for real-world challenges in the maritime industry.